Production of nata from rambutan (Nephelium lappaceum) pulp. - Daywan, Abigail Diesca (2016.)
Rambutan is a seasonal fruit in the Philippines. Being highly perishable, a lot of the harvest goes to waste if it could not be marketed within 3-5 days. This study intended to explore the utilization of Rambutan pulp to produce a bacterial cellullose commonly called ?Nata?, thus will contribute to the reduction of Rambutan fruit waste. The Rambutan pulp was characterized in terms of Total Soluble Solids (TSS), % Titratable Acid (%TA), pH, and moisture content before processing into Nata at different periods of fermentation: designated as F8 and F12 for 8 and 12 days of fermentation respectively. The produced Nata was analyzed for TSS, %TA, pH, and moisture content and Best Nata Yield (BNY) based on weight. The sensory characteristics of the BNY was determined. Paired t-test 5% significance level, showed significant differences in the physico-chemical properties between Rambutan samples obtained from Bo. Conception, Talisay (as sample T) and from Banga, Aklan (as sample V). One-way ANOVA at 5% level, showed significant differences in the physico-chemical properties and yield of Nata among all treatments. R2 for physico-chemical properties were low. The BNY was treatment BF12. The cooked BNF was described as ?like very much? with attributes as ?moderately soft?, ?moderately smooth? and ?clear-white?.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Rambutan; Nephelium lappaceum; Nata